1987
DOI: 10.1111/j.1348-0421.1987.tb03066.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Demonstration and Isolation of Ribosomes in Mesosomes from Staphylococcus aureus

Abstract: Mesosomes of Staphylococcus aureus 209P were observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The purified mesosomal preparation was composed of closed, short tubules and vesicles (Fig. 2a), indicating that fragmentation occurred during the isolation process, since mesosomes were long and branched tubular structures in situ (4,17,27). The mesosomal vesicles and tubules isolated here were not penetrated by the negative stain, indicating that they were packed with contents.…”
Section: Isolation and Morphology Of Mesosomesmentioning
confidence: 95%
See 2 more Smart Citations
“…The purified mesosomal preparation was composed of closed, short tubules and vesicles (Fig. 2a), indicating that fragmentation occurred during the isolation process, since mesosomes were long and branched tubular structures in situ (4,17,27). The mesosomal vesicles and tubules isolated here were not penetrated by the negative stain, indicating that they were packed with contents.…”
Section: Isolation and Morphology Of Mesosomesmentioning
confidence: 95%
“…M-ribosomes have the same sedimentation profile and morphological appearance as C-ribosomes. In S. aureus we previously showed that M-ribosomes could not be distinguished in morphological images as well as in sedimentation profiles from C-ribosomes (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its aggressiveness and to the existence and proliferation of many multidrug-resistant strains, S. aureus is a major public health concern [13]. To our knowledge, only S. aureus ribosomes and not the polysomes have been studied [4,[14][15][16][17][18].…”
mentioning
confidence: 99%